Delta Neutrophil Index as a Marker for Differential Diagnosis between Acute Graft Pyelonephritis and Acute Graft Rejection. - Dong Ho Shin (PLoS ONE, 2015)
The delta neutrophil index (DNI) is the fraction of circulating immature granulocytes, which reflect infectious and/or septic condition. Acute graft pyelonephritis (AGPN) versus acute graft rejection is a frequently encountered diagnostic and therapeutic dilemma in kidney transplant recipients, but little is known about the clinical usefulness of DNI value in the differentiation of the two conditions.A total of 90 episodes of AGPN or acute graft rejection were evaluated at the Kangdong Sacred Heart Hospital between 2008 and 2014. We performed retrospective analysis of demographic, clinical, and laboratory parameters data. Receiver operating curves (ROC) and multivariate logistic regression were conducted to ascertain the utility of DNI in discriminating between AGPN and acute graft rejection.AGPN group had significantly higher DNI values than acute graft rejection group (2.9% vs. 1.9%, P < 0.001). The area under the ROC curve for DNI value to discriminate between AGPN and acute graft rejection was 0.85 (95% confidence interval [CI]; 0.76-0.92, P < 0.001). A DNI value of 2.7% was selected as the cut-off value for AGPN, and kidney transplant recipients with a DNI value ≥ 2.7% were found to be at a higher risk of infection than those with a DNI < 2.7% (odd ratio [OR] 40.50; 95% CI 8.68-189.08; P < 0.001). In a multivariate logistic regression analysis, DNI was a significant independent factor for predicting AGPN after adjusting age, sex, log WBC count, log neutorphil count, log lymphocyte count, CRP concentration, and procalcitonin concentration (OR 4.32; 95% CI 1.81-10.34, P < 0.001).This study showed that DNI was an effective marker to differentiate between AGPN and acute graft rejection. Thus, these finding suggest that DNI may be a useful marker in the management of these patients.